Analysis of The Implementation of Green Banking in Islamic Banks (Empirical Study On Indonesian Sharia Bank KCP Kabanjahe) - Cindy Anggreni; Ahmad Syakir; Tuti Anggraini (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The purpose of this research is to find out how Green Banking is applied to the policies and financing options offered by Bank Syariah Indonesia KCP Kabanjahe and has been utilized to execute the idea of Green Banking. The method used in this research is field research using a qualitative descriptive research approach. Data obtained from researchers' interviews with Bank Syariah Indonesia informants were analyzed in this research. Research findings show that Bank Syariah Indonesia KCP Kabanjahe has adopted a policy of implementing environmentally friendly banking which includes internal training on this matter, modification of the bank's IT infrastructure, and management style. Implementation of green banking in distribution at Bank Syariah Indonesia KCP Kabanjahe, financing is provided by reducing social and environmental hazards as well as evaluating customers' environmental documentation for financing applications. The Small and Medium Enterprises (UKM) market sector receives an environmentally friendly guarantee in the form of ownership of environmental documents from the Indonesian Sharia Bank Office KCP Kabanjahe.